Pembuatan Obi Modifikasi Berbahan Crinoline dengan Aplikasi Bordir - Sholekah, Andawiyah Fatikhatus; Arifiana, Deny (Institut Seni Indonesia Yogyakarta, 2024)
The purpose of this research is to find out how the process of making obi made of crinoline with embroidery applications, and find out the results of making obi made of crinoline with embroidery applications. This study uses the method of creation of work which is divided into four stages. The first is the pre-design stage. Second, the design stage. Third, the embodiment stage. Fourth, the presentation stage. This research resulted in the process of making obi made of crinoline starting from making designs, making patterns, laying patterns and cutting materials, sewing. The process of making embroidery applications begins with making designs, working on embroidery applications by embroidery craftsmen, cutting embroidery applications according to the design. The process of applying the embroidery application to the obi made from crinoline begins with laying the embroidery application, then installing the embroidery application using a sum stitch with the help of a needle and string thread. The finished result of making an embroidery application on a crinoline obi is not in accordance with the source of ideas and designs that have been made.ABSTRAKTujuan dari penelitian ini ialah untuk mengetahui bagaimana proses pembuatan obi berbahan crinoline dengan aplikasi bordir, dan mengetahui hasil pembuatan obi berbahan crinoline dengan aplikasi bordir. Penelitian ini menggunakan metode penciptaan karya yang terbagi menjadi empat tahap. Pertama yaitu tahap pra-perancangan. Kedua, tahap perancangan. Ketiga, tahap perwujudan. Keempat, tahap penyajian. Penelitian ini menghasilkan proses pembuatan obi berbahan crinoline dimulai dari pembuatan desain, pembuatan pola, peletakan pola dan memotong bahan, menjahit. Proses pembuatan aplikasi bordir dimulai dengan pembuatan desain, pengerjaan aplikasi bordir oleh pengrajin bordir, pemotongan aplikasi bordir sesuai dengan desain. Proses penerapan aplikasi bordir pada obi berbahan crinoline dimulai dengan peletakan aplikasi bordir, lalu pemasangan aplikasi bordir dengan menggunakan tusuk sum dengan alat bantu jarum dan benang senar. Hasil jadi pembuatan aplikasi bordir pada obi berbahan crinoline kurang sesuai dengan sumber ide dan desain yang telah dibuat.